A Perceção do Consumidor face à Comunicação das Marcas de Moda de Luxo nas Redes Sociais - Cunha, Maria Nascimento (2019)
Luxury fashion brands have been studied in several areas, such as Marketing, Communication, History and even Sociology, and today they are represented through social networks. The objective of the research that is presented here is to understand consumer perception of the communication of luxury fashion brands through social networks.In the present investigation, a quantitative methodology based on a questionnaire survey based on an instrument with validity and reliability is used, although adapted from Yadav and Rahman (2017) to a new context (social media marketing of luxury brands) and to a population (Portuguese), was shown to be adequate to measure consumer perception of the communication of luxury fashion brands in social networks. The sample collected consists of 580 consumers of luxury fashion brands in social networks. The analysis of the model of structural equations showed that the perception scale of consumers of luxury fashion brands in social networks constituted by five dimensions (Interactivity, Information Capacity, Personalization, Trendinessand Password), presents adequate levels of validity and reliability.